Estudo da norma escrita brasileira presente em textos jornalísticos e técnico-científicos - Rosangela Borges Lima (2003)
This work aims at contributing for the scientific description of WrittenStandard Brazilian Portuguese at the present time; also aiming at creating reference materials for tlie user of Portuguese who needs to use the standard variety of the language in his or her work of writing and reviewing texts; creating didactic materials for tlie teaching of Portuguese; improving the teaching of Portuguese, so that teaching is structured taking into account today's linguistic reality.So as to reach these goals, the standard written variety of Poituguese will be studied as it is used in teclmical-scientific and journalistic texts. The following steps are to be taken; once grammatical topics judged to be more relevant have been selected, research will be done in tiaditional grammars, in nonnative manuals for the use of Portuguese (dictionaries and books of "correct language") and in manuals of style and omposition usually followed in pails of the Brazilian press. Research will then establish convergent and divergent views as presented in tliese eferenceworks. After the corpus has been collected, occurrences of linguistic facts will be divided into two classes: those that conespond to the canonical norm and those tliat depart from it. Data thus gathered will be tlien interpreted in tenns of percentile so as to establish patterns for Standard Written Brazilian Poituguese actually used by present-day educated Brazilians.